리나글립틴 하이드록시신남산 공결정의 제조와 특성 - 서명원 (The Graduate School, Ajou University, 2019)
국문 초록 디펩티딜 펩티다제-4 (dipeptidyl peptidase-4, DPP-4) 억제제인 리나글립틴 (linagliptin)은 제2형 당뇨병의 치료에 사용된다. 현재 사용되는 활성 성분은 결정형 A형과 B형의 혼합물을 함유하는 유리 염기 (리나글립틴 유리 염기 A/B) 형태이다. 이러한 두가지 결정 형태가 상온에서 상전이 되기 때문에 장기안정성에 대한 우려가 있다. 본 연구에서는 결정형 상전이 문제를 극복하고자 하이드록시신남산류를 이용하여 리나글립틴의 하이드록시신남산염 합성을 시도하였다. 리나글립틴-페룰린산, 리나글립틴-이소페룰린산 및 리나글립틴-3,4-디메톡시신남산은 기대하던 염이 아닌 공결정으로 얻어졌으나, 카페산염과 쿠마르산염은 고체결정으로 얻어지지 않았다. 얻어진 공결정의 고체상 안정성시험에서 리나글립틴–페룰린산과 리나글립틴-3,4-디메톡시신남산은 매우 우수한 열 안정성을 보였다. 광 안정성시험에서 리나글립틴-페룰린산은 좋은 광 안정성을 보여주었으나 리나글립틴-3,4-디메톡시신남산은 상대적으로 낮은 광 안정성을 보였다. 이 결과, 리나글립틴-페룰린산 공결정이 열 안정성과 광 안정성을 동시에 갖고 있음이 확인되었다. 페룰린산이 어떻게 리나글립틴 유리 염기의 안정성을 향상시키는지 알아보기 위해 싱크로트론 X-선 분말 회절 (SXPD) 분석을 수행하였다. 리나글립틴-페룰린산 공결정의 결정구조는 2 개의 리나글립틴과 2 개의 페룰린산 분자의 결정 패킹에 의해 구성되어 있으며, 결정계는 단사정계이며 공간그룹은 P 21이다. 2 개의 리나글립틴과 1 개의 페룰린산 분자는 π-π 적층되어 있으며 ab 평면을 따라 연장되어 지그재그 접힌 시트 구조를 형성한다. 다른 페룰린산 분자 1 개는 시트 사이에 위치한다. 리나글립틴 분자의 크산틴기는 다른 리나글립틴 분자의 퀴나졸린기와 약 4.3 Å의 거리로 π-π 적층 되어있다. 리나글립틴-페룰린산 공결정의 증가된 안정성은 그 결정 구조에서 리나글립틴과 페룰린산 사이의 π-π 적층으로부터의 추가적인 분자 간 상호작용에 기인한 것일 수 있다. 추가적인 약리학적 평가에서, 리나글립틴-페룰린산 공결정은 리나글립틴 유리 염기 A/B와 유사한 독성, 투과도 및 약동학적 성질을 가지고 있음이 확인되었다. 따라서 리나글립틴-페룰린산 공결정은 약리적인 성질을 유지하면서 리나글립틴 유리 염기의 불안정한 문제를 해결할 수 있는 적합한 공결정일 수 있다. Abstract Linapliptin is a dipeptidyl peptidase-4 (DPP-4) inhibitor used in the treatment of type 2 diabetes. The active ingredient of linagliptin currently in use is the free base form containing a mixture of polymorph A and B (linagliptin base A/B). Since these two polymorphs interconvert at room temperature, there is still a concern about long-term stability. In this study, the synthesis of hydroxycinnamate of linagliptin was attempted to overcome the problem of polymorphic phase transition by using hydroxycinnamic acid. Accordingly, linagliptin-ferulic acid, linagliptin-isoferulic acid, and linagliptin-3,4-dimethoxycinnamic acid were obtained as cocrystals rather than the expected salts, but caffeate and coumarate were not obtained as solid crystals. From the solid-state thermal stability tests of the obtained cocrystals, linagliptin-ferulic acid and linagliptin-3,4-dimethoxycinnamic acid showed very good thermal stability. In the photostability test, linagliptin-ferulic acid showed good photostability while linagliptin-3,4-dimethoxycinnamic acid showed relatively low photostability. These results confirmed that linagliptin-ferulic acid cocrystal has both thermal stability and photostability. In order to investigate how ferulic acid improved the stability of linagliptin free base, synchrotron X-ray powder diffraction (SXPD) was performed. The crystal structure of linagliptin-ferulic acid cocrystal is constructed by the crystal packing of two linagliptin and two ferulic acid molecules, and the crystal system is monoclinic and the space group is P21. Two linagliptin molecules and one ferulic acid molecule are π-π stacked and extended along the ab plane to form a zigzag folded sheet structure. One other ferulic acid molecule is located between the sheets. The xanthine group of a linagliptin molecule is π-π stacked at a distance of about 4.3 Å from the quinazoline group of another linagliptin molecule. Thus, the increased stability of linagliptin-ferulic acid cocrystal may be due to additional intermolecular interactions from the π-π stacking between linagliptin and ferulic acid in its crystal packing structure. In an additional pharmacological evaluation, linagliptin-ferulic acid cocrystal had similar toxicity, permeability and pharmacokinetic properties to linagliptin base A/B. Therefore, linagliptin-ferulic acid can be a suitable cocrystal form that overcomes the problem of instability of linagliptin base while maintaining the pharmacological properties.
학위논문(박사)--아주대학교 일반대학원 :분자과학기술학과,2019. 8